Santri Entrepreneurial Model and its Implementations as Community Empowerment Programs - Ansori Ansori; Mustofa Kamil; Achmad Hufad (Journal of Nonformal Education, 2023)
The challenges in local community development and the need for innovative solutions in entrepreneurship training and education form the crucial foundation for this research. The objective of the study is to determine the effect of the entrepreneurial model of Santri (students of Islamic Boarding School) on the empowerment of the community around the Miftahul Ihsan Islamic Boarding School. The research used quasi experimental method. The instruments of the study are observation, interviews, questionnaires. The data analysis technique used in this study is the linear regression test and the t test. The sample are 200 students of Miftahul Ihsan Islamic boarding school. Based on the results of the study found that (1) the influence of entrepreneurial students showed a very strong and significant relationship toward community empowerment indicated premises n the value of t count is 27,720 and the value of t table with df = 198 and α = 0 , 05 is 1.972. (2) Thera are difference in the community development group that uses Santri entrepreneurial model and group with conventional entrepreneurial model, it is indicated by the average of gain score in the experimental group that is 0.53, it is higher than in the control group that shows 0.01. The conclusion is that Santri entrepreneurial model effective in promoting community empowerment in Miftahul Ihsan Pesantren (Islamic Boarding School). The implication of this research is that community empowerment through the entrepreneurial model of Santri can build a new system for community structure as an effort to optimize natural potential and human resources so that people can contribute to community development